Biosorption of mercury from aqueous solution and oilfield produced water by pristine and sulfur functionalized rice residues. Issue 5 (23rd March 2015) - Song, Shiow‐Tien; Saman, Norasikin; Johari, Khairiraihanna; Mat, Hanapi
Abstract : This article presents the biosorption potential of rice residues for Hg(II) removal from aqueous solution and oilfield produced water. Rice husk and rice straw were selected and functionalized with sulfur group from carbon disulfide in alkaline condition. The raw and modified biosorbents were characterized by using scanning electron microscopy, fourier transform infrared spectroscopy, energy dispersive X‐ray, and X‐ray photoelectric spectroscopy. Batch biosorption experiments were carried out to evaluate the effects of pH, initial ion concentration, contact time, and temperature on the removal process. It was found that the biosorption of rice residues showed a significant improvement in Hg (II) biosorption performance after the functionalization treatment. The maximum Hg(II) capacity of sulfur‐functionalized rice straw (RSS) and sulfur‐functionalized rice husk (RHS) obtained under present experiment condition was 119 and 92 mg/g, respectively. The equilibrium data were best‐fitted to Langmuir isotherm model, while the kinetic data followed the pseudo‐second‐order kinetic model. The biosorption process was endothermic, feasible and spontaneous in nature. The biosorbents showed good selectivity towards Hg(II) biosorption from the oilfield produced water. © 2015 American Institute of Chemical Engineers Environ Prog, 34: 1298–1310, 2015